Mappe dei contagi e condizioni eco-territoriali - Malcevschi, Sergio; Santolini, Riccardo; Paris, Gianmarco; Pluchino, Paola (Scienze del Territorio, 2020)
The article presents the maps and data at the provincial level of COVID infections in Italy in the first phase of the epidemic (March-May 2020). The bio-geography of infections in Italy was very articulated, with a spatial imprint that was maintained in the months considered despite significant variations in the total number of infections within the period considered. In addition to a North-South macro-gradient, infra- and supra-regional territorial areas with specific characteristics have been produced. The situations less affected by the infections occurred in areas without significant metropolitan components, characterized by a more balanced relationship from an ecological and landscape point of view. Some implications for better management of future epidemic risks are discussed. The so-called ‘green deal’ development models, in addition to the new contents for economic productions, need to have greater awareness of the bio-physical risks associated with an inadequate government of the territory: it will be necessary that they concretely assign a relevant role to multi-scalars networks of ecosystems and landscapes and the resilience services they offer.